Black Race as a Social Determinant of Health and Outcomes After Lumbar Spinal Fusion Surgery: A Multistate Analysis, 2007 to 2014. Issue 10 (15th May 2020) - Aladdin, Dima El Halawani; Tangel, Virginia; Lui, Briana; Pryor, Kane O.; Witkin, Lisa R.; White, Robert S.
Abstract : Study Design: A retrospective analysis of patient hospitalization and discharge records. Objective: To examine the association between race and inpatient postoperative complications following lumbar spinal fusion surgery. Summary of Background Data: Racial disparities in healthcare have been demonstrated across a range of surgical procedures. Previous research has identified race as a social determinant of health that impacts outcomes after lumbar spinal fusion surgery. However, these studies are limited in that they are outdated, contain data from a single institution, analyze small limited samples, and report limited outcomes. Our study aims to expand and update the literature examining the association between race and inpatient postoperative complications following lumbar spine surgery. Methods: We analyzed 267, 976 patient discharge records for inpatient lumbar spine surgery using data from the Healthcare Cost and Utilization Project's State Inpatient Databases for California, Florida, New York, Maryland, and Kentucky from 2007 through 2014. We used unadjusted bivariate analysis, adjusted multivariable, and stratified analysis to compare patient demographics, present-on-admission comorbidities, hospital characteristics, and complications by categories of race/ethnicity. Results: Black patients were 8% and 14% more likely than white patients to experience spine surgery specific complications (adjusted odds ratios [aOR]: 1.08, 95% confidence interval [CI]: 1.03–1.13) and general postoperative complications (aOR: 1.14, 95% CI: 1.07–1.20), respectively. Black patients, compared with white patients, also had increased adjusted odds of 30-day readmissions (aOR: 1.13, 95% CI: 1.07–1.20), 90-day readmissions (aOR: 1.07, 95% CI: 1.02–1.13), longer length of stay (LOS) (adjusted Incidence Rate Ratio: 1.15, 95% CI: 1.14–1.16), and higher total charges (adjusted Incidence Rate Ratio: 1.08, 95% CI: 1.07–1.09). Conclusion: Our findings demonstrate that black patients, as compared with white patients, are more likely to have postoperative complications, longer postoperative lengths of stay, higher total hospital charges, and increased odds of 30- and 90-day readmissions following lumbar spinal fusion surgery. Level of Evidence: 4 Abstract : Supplemental Digital Content is available in the textBlack race is a social determinant of health that impacts outcomes after lumbar spinal fusion surgery. We showed that black patients, as compared with white patients, are more likely to have postoperative complications, be readmitted, have longer lengths of stay, and have higher total hospital charges.